Madrasah Principal Leadership Management In Developing Human Resources - Ropida Batubara; Tien Rafida; Toni Nasution (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyze the leadership management of the madrasa principal in developing human resources at Al Qomariah Islamic Boarding School in Galang. Human resource development is one of the important factors in improving the quality of education in madrasa institutions; therefore, effective and well-directed leadership from the madrasa principal is required. This research uses a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation involving the madrasa principal, teachers, and educational staff at Al Qomariah Islamic Boarding School, Galang. The collected data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the leadership management of the madrasa principal in developing human resources is carried out through several strategies, including planning programmes for teacher competency development, implementing continuous training and guidance, providing motivation, and conducting periodic performance evaluations. In addition, the madrasa principal applies a participatory leadership pattern by involving all elements of the madrasa in decision-making processes. These efforts have an impact on increasing the professionalism of teachers and educational staff, as well as creating a conducive working environment in the madrasa. Therefore, the leadership management of the madrasa principal plays a very important role in improving the quality of human resources at Al Qomariah Islamic Boarding School, Galang